An HS-GC-IMS analysis of volatile flavor compounds in brown rice flour and brown rice noodles produced using different methods. (1st May 2022) - Sun, Zhouliang; Lyu, Qingyun; Chen, Lei; Zhuang, Kun; Wang, Guozhen; Ding, Wenping; Wang, Yuehui; Chen, Xi
Abstract: In this study, headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) and principal component analysis (PCA) were used to analyze the volatile flavor compounds in brown rice flour (BRF) and brown rice noodles (BRNs) prepared by different methods. White rice flour (WRF) and white rice noodles (WRNs) were used for comparison. The results revealed significant differences in volatile flavor compounds between BRFs and BRNs, and the types of volatile flavor compound in BRF were more than WRF. Compared with WRF, aldehydes increased in the BRF produced by refilling. The primary volatile flavor compounds of brown rice flour made by crushing brown rice fully (BRF-F) were 2-acetyl-1-pyrroline, 6-methyl-5-hepten-2-one, 2-heptanone, 2, 3-butanedione, 2-octanone, 2-butanone, 1-hexanol, 1-pentanol, ethanol, 2-methylbutanol, 3-methylbutanol, and 2-methylpropanol. Ethyl acetate was found in all rice flour and rice noodle samples. The contents of 2-methylpropanol, 2-hexanone, 2-methylbutanal, 3-methylbutanal, ethanol and acetone increased after processing rice flour into rice noodles, while the contents of 2-acetyl-1-pyrroline, 6-methyl-5-hepten-2-one, 1-hexanol, 2-heptanone, 1-pentanol and 2, 3-butanedione decreased. This research demonstrated the promising application of extrusion in fabricating brown rice flour with satisfactory flavor preservation for refilling in WRF. Graphical abstract: Image 1 Highlights: Proposed a method combined semidry process with refilling to produce brown rice flour. Found a rapid identification method of volatile organic compounds in brown rice flour. The volatile flavor compounds beneficial to health in brown rice will not disappear during the extrusion of rice bran. 2-Pentyl furan reduced or even disappeared after the rice bran was extruded. Demonstrated a promising application of extrusion in fabricating the brown rice flour with satisfied flavor.